2017
DOI: 10.1007/s11605-016-3344-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Viral Etiology on Postoperative De Novo Recurrence After Hepatectomy for Hepatocellular Carcinoma in Cirrhotic Patients

Abstract: HCV-related LC was associated with a higher postoperative de novo carcinogenesis than HBV-related LC. Establishment of different treatment algorithms as well as follow-up surveillance protocols stratified by viral etiology may be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…There are not many differences compared to the recurrence pattern of the untreated group in the present study. HCV-associated hepatocellular carcinoma tends to develop multicentric carcinogenesis more frequently than other causes of hepatocellular carcinoma [31,32]. In other AST aspartate aminotransferase, ALT alanine aminotransferase, PLT platelets, PT prothrombin time, T.Bil total bilirubin, Alb albumin, AFP alpha-fetoprotein, HCC hepatocellular carcinoma, DAA direct-acting antiviral agent J Gastroenterol words, eradication of HCV by DAA suppresses multiple recurrences after HCC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…There are not many differences compared to the recurrence pattern of the untreated group in the present study. HCV-associated hepatocellular carcinoma tends to develop multicentric carcinogenesis more frequently than other causes of hepatocellular carcinoma [31,32]. In other AST aspartate aminotransferase, ALT alanine aminotransferase, PLT platelets, PT prothrombin time, T.Bil total bilirubin, Alb albumin, AFP alpha-fetoprotein, HCC hepatocellular carcinoma, DAA direct-acting antiviral agent J Gastroenterol words, eradication of HCV by DAA suppresses multiple recurrences after HCC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-HBV therapy Although the advance in the treatment of HCC provides opportunities for curative treatment, a high incidence of recurrence, up to 50% at 5 years after curative treatment, was observed in patients with underlying chronic HBV infection [104] . Therefore, it is urgent to identify risk factors associated with HCC recurrence and develop tertiary prevention for HBV-related HCC after curative treatment.…”
Section: Tertiary Preventionmentioning
confidence: 99%
“…The high rate of recurrence remains a challenge for hepatic surgeons. Risk factors related with tumour characteristics are significantly related to early HCC recurrence, but the impact of viral status on recurrence is unclear, and some studies did not identify any role for hepatitis B viral status on prognosis, whilst other studies suggested that the presence of HBeAg was significantly correlated with prognosis . Propensity score matching analysis has been widely used in patients with HCC .…”
Section: Introductionmentioning
confidence: 99%